Expression of pathogenicity-related genes of Xylella fastidiosa in vitro and in planta - de Souza, A. A.; Takita, M. A.; Pereira, E. O.; Coletta, H. D.; Machado, M. A. (Springer, 2005)
Xylella fastidiosa is responsible for several economically important plant diseases. It is currently assumed that the symptoms are caused by vascular occlusion due to biofilm formation. Microarray technology was previously used to examine the global gene expression profile of X. filstidiosa freshly isolated from symptomatic plants or after several passages by axenic culture medium, and different pathogenicity profiles have been obtained. In the present study the expression of some pathogenicity-related genes was evaluated in vitro and in planta by RT-PCR. The results suggest that adhesion is important at the beginning of biofilm formation, while the genes related to adaptation are essential for the organism's maintenance in planta. Similar results were observed in vitro mainly for the adhesion genes. The pattern of expression observed suggests that adhesion modulates biofilm formation whereas the expression of some adaptation genes may be related to the environment in which the organism is living.